Easily Missed: A Case Series of New Heart Failure in Young Adults. (23rd August 2020) - Hall, Eric J.; Menachem, Jonathan; Stevenson, Lynne Warner; Huston, Jessica
Abstract : Background . While uncommon, heart failure (HF) can present in young adults from a variety of causes. Identifying HF in a young patient presents many challenges, the foremost of which is recognition of the signs and symptoms of HF. Case Summary . We present four cases of new diagnosis of HF (due to familial cardiomyopathy, tachycardia-induced cardiomyopathy, spontaneous coronary artery dissection, and peripartum cardiomyopathy) to highlight the range of etiologies and presentations requiring recognition in this patient population. Discussion . A high index of suspicion is needed to diagnose HF in young adults, who may not present with classic signs and symptoms. Young adults represent a unique patient population that differs from the older patients with HF. Young adults with newly diagnosed HF should be promptly referred to a center offering full diagnostic capabilities and advanced cardiac therapies.